Central mucoepidermoid carcinoma in a young patient: A case report and review of the literature. Issue 1 (January 2016) - Del Corso, G.; Pizzigallo, A.; Marchetti, C.; Tarsitano, A.
Abstract: Background: Central mucoepidermoid carcinoma is a rare malignant salivary neoplasm arising inside the bone of the jaws. We report a rare case of central mucoepidermoid carcinoma of a 16-year-old girl arising in the maxilla. Clinical and radiological analyses were shown and discussed, as well as the surgical treatment. Methods: A left maxillectomy from the last molar to the first premolar was performed, and the site was reconstructed using a fibula free flap stabilized with titanium plates. Results: The young patient was followed up for more than 6 years, and to date no recurrence was observed. A literature review of the 11 rare previous cases was provided to guide the clinician in the diagnosis and management of this unusual glandular tumor. Conclusion: It is of immense importance to differentiate the central mucoepidermoid from other osteolytic lesion and odontogenic cysts because of his malignancy and local aggressiveness. The treatment option is the radical excision, with the evaluation of neck nodes, and radiotherapy is only recommended in the most aggressive of cases.